Differences in Post-Operative Complaints between Patients with and without Anatomical Variations of Ostiomeatal Complex Based on CT Scan of Chronic Rhinosinusitis at Dr. Moewardi Hospital - Putro, Prasetyo Sarwono; Duswanto, Yudo; Wujoso, Hari; Soewondo, Widiastuti (Indonesian Journal of Medicine, 2021)
Background: The ostiomeatal complex has various anomalous variants that can vary in type and number for each person. These anomalies can contribute to the development of chronic rhinosinusitis and the accompanying symptoms. This study aims to determine the differences in post-treatment complaints between patients with and without anatomical variations of the ostiomeatal complex in chronic rhinosinusitis at RSUD Dr. Moewardi.Subjects and Method: A cross-sectional study was conducted in Dr. Moewardi hospital, Surakarta. A sample of 30 of chronic rhinosinusitis patients who were subjected to a CT scan in the radiology department and surgery by an ENT-KL specialist at Dr. Moewardi, from January 2019 to June 2020, was selected for this study. The study variables were anatomical variations of ostimeatal complex and post-operative complaints. Difference of post-operative complaints between chronic rhinosinusitis patients with and without anatomical variations of ostiomeatal complex were described in frequency (n) and percent (%).Results: This study indicated that there is no difference in post-operative complaints between patients with and without anatomical variations of the ostiomeatal complex based on CT Scan of chronic rhinosinusitis (p= 0.856).Conclusion: There is no difference in post-operative complaints between patients with and without anatomical variations of the ostiomeatal complex based on CT Scans of chronic rhinosinusitis.Keywords: ostiomeatal complex, CT scan, post-operative complaintsCorrespondence: Yudo Duswanto. Department of Radiology, Dr. Moewardi Hospital, Surakarta, Indonesia. Email: yudoduswanto7@gmail.com.Indonesian Journal of Medicine (2021), 06(02): 212-219https://doi.org/10.26911/theijmed.2021.06.02.10